Multinational Review of English Language Disability Studies Degrees and Courses - Pamela Cushing; Tyler Smith (Disability Studies Quarterly, 2009)
This article provides a longitudinal account of the growth of disability studies (DS) as an academic field, focusing on DS degrees and courses in the United States, Canada, the United Kingdom, Australia, and New Zealand. We discuss emerging patterns in the field including the disciplines where DS is commonly housed. The data tables can be revised as the field evolves. We found that the field is expanding at an exponential rate with three key dimensions of growth: independent DS departments, hybridization with applied disciplines, and integration within the liberal arts. In our analysis, we highlight various questions that call for further dialogue and debate.